ON M2 SURFACES OF BIHARMONIC B-GENERAL HELICES ACCORDING TO BISHOP FRAME IN HEISENBERG GROUP Heis3 - Korpinar, Talat; Turhan, Essin (Univ Nis, 2012)
In this paper, we study M-2 surfaces of biharmonic B-general helices according to Bishop frame in the Heisenberg group Heis(3). Finally, we characterize the M-2 surfaces of biharmonic B-general helices in terms of Bishop frame in the Heisenberg group Heis(3).